Review of bacteriophage and its applications - Soressa Bakala Gamachu; Motuma Debalo (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
The most prevalent and ubiquitous organisms in the world are bacteria-killing viruses called bacteriophages. The aim of this paper is to highlight some application areas of bacteriophages. There are both virulent and temperate bacteriophages in the environment, but only virulent bacteriophages are used for treatment, known as phage therapy. Since their discovery, bacteriophages have been considered a vital weapon to fight human and animal illnesses of bacterial origin. Currently, the emergence of growing microbial resistance to antibiotics and attention to bacteriophage use in treatment has all but grown up again. Correspondingly, the applications of bacteriophages for biocontrol purposes have become a remarkable opportunity in a number of fields, including farms and food production. Despite their treatment effects, bacteriophages also maintain a vital relationship with their hosts through moderating microbial populations and promoting their evolution by horizontal gene transfer. Additionally, they serve as vehicles for the transfer of vaccinations, the detection of dangerous microorganisms and systems for displaying proteins and antibodies. Bacteriophages are a varied collection of viruses that are simple to handle, making them suitable for use in treatments and biotechnology research. Hence, the expansion of various phage companies for phage production and the use of phage cocktails for the treatment of various bacterial diseases at different stages is recommended.